Dynamical properties of environmental high-performance composites with calcined clay. (10th February 2022) - Wei, Jingjie; Long, Wu-Jian; Khayat, Kamal H.; Dong, Biqin; Mei, Liu; Xing, Feng
Abstract: Concrete structures may be exposed to dynamic loadings within short periods such as earthquakes and vehicles load, resulting in substantial damage to human life and property because of the collapse of concrete structures. The research achievements on dynamic properties of high-performance composites with LC 3 (HPC-LC 3 ) are limited, although dynamic loadings are commonly encountered in infrastructure. The study aims to develop a new-green concrete product (HPC-LC 3 ) with high dynamical properties and promote its mass use in a vibration service environment by investigating dynamical properties of HPC-LC 3 . Dynamical properties of structure can be promoted at material level by means of enhancing the inherent ability of cement-matrix materials to passively absorb the vibrational energy. Dynamic properties of traditional HPC may be improved by incorporated LC 3 because of excellent mechanical properties. The fiber pull-out, thermogravimetric analysis (TGA), (nuclear magnetic resonance) NMR, and microstructure test were used to reveal the enhanced mechanism of dynamic properties in the HPC with LC 3 (HPC-LC 3 ), and the economic efficiency of HPC is also evaluated to promote its mass application. The results indicate that the dynamic properties of HPC-LC 3 increased by 47% in damping capacity, 102% in storage modulus, 16% in energy dissipation, in comparison with the reference (HPC-OPC). Meanwhile, compared with the reference, the compressive and flexural strengths of LC 3 -50 increased by 14% and 27%. TGA and NMR results indicate that LC 3 -50 shows better hydration characteristics, longer alumina-silicate chain length (from 3.9 to 8) than HPC-OPC. The proposed composites reduced embodied energy, embedded CO2 emissions, and costs of HPC by up to 33%, 45%, and 7%, respectively. Thus, the green product (HPC-LC 3 ) with 30%–40% calcined clay, high dynamic properties and more sustainable, will be recommended to mass use in a vibration service environment. Graphical abstract: Image 1 Highlights: Dynamic properties and ecology were coupled to evaluate calcined clay (CC) dosage. Dynamic mechanical properties of HPC increased significantly with LC 3 addition. Maximum reduction of EE, ECO2 and cost were 33, 45 and 7%, compared to reference. 30%–40% CC was suggested for higher dynamic properties and ecological benefits.